Knowledge, attitude and practice on functional food consumption among health science and non-health science students - Mat Jusoh, Hanapi; Noor Azman, Noor Aziemah (International Islamic University Malaysia, 2023)
Introduction: It is widely recognized that functional foods can address specific health needs of consumers, potentially contributing to enhancing overall public health. While numerous studies have explored consumer perception and acceptance of functional food products, research examining knowledge, attitude, and practice (KAP) remains limited, especially among university students. Hence, this study aimed to assess KAP regarding functional foods consumption among both health science and non-health science students. Methods: A total of 118 students participated in this study, including 77 from the health science group and 41 from the non-health science group. Respondents were provided with a self-administered questionnaire that covered demographic profiles, knowledge, attitude, and practice related to functional foods consumption. Results: The study showed that students at IIUM Kuantan exhibited poor knowledge, moderate attitude, and poor practice regarding functional foods consumption. Notably, health science respondents demonstrated significantly higher levels of knowledge and attitude compared to their non-health science counterparts. Interestingly, both groups showed a similar frequency of functional foods consumption per week. Conclusion: Overall, students at IIUM Kuantan had poor levels of knowledge, moderate attitude, and practice about functional foods intake, although health science groups had higher knowledge and attitude than non-health science groups. Additional efforts are needed to increase knowledge and awareness regarding the consumption of functional foods.